Risk and outcome of Sepsis Associated Encephalopathy after Acute Gastrointestinal Perforation - Zhou Ye-ting§; Tong Dao-ming§; Ye Song; Zhang Li-fei; Xu Ben-wen; Yang Chen- xi (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Sepsis associated encephalopathy (SAE) is the most common encephalopathy in ICU and may contribute to a high mortality. Few data are available on the risk and outcome of SAE after patients with gastrointestinal (GI) perforation. We reviewed all patients admitted to our department of general surgery with GI perforation over a 3-year period. We used the sepsis-related organ failure criteria for diagnosis of SAE (GCS<13 score in absence of sedation). Exclusion criteria were present evidence of meningitis/ encephalitis and other primary encephalopathy. Of 58 patients admitted for GI perforation during the study period, 22 patients (37.9%) developed sepsis. Of them, 9 (40.9%) patients (7 male, mean 79y) had SAE according to the inclusion/exclusion criteria. The presence of SAE was significantly associated with increased age (79.0±11.3 vs. 59.6 ±16.3, p=0.006), lower mean arterial pressure (MAP) (70.7±15.3 vs. 90.4.±16.8, p=0.000), lower GCS score (9.7±3.6 vs. 15±0.0, p=0.000), elevated SOFA score (8.9±3.3 vs. 3.6±1.6, p=0.000) and qSOFA score (1.9±0.3 vs. 0.4 ±0.5, p=0.000), and higher mortality at 30 days (66.7% vs. 7.7%, P=0.000). Nevertheless, in Cox regression analysis, only a lower MAP was associated with worse survival in SAE. Sepsis occurred in 37.9% of patients after GI perforation. These patients had more frequent SAE and needed more aggressive ICU therapy; a lower MAP is significantly influence outcome.